2016
DOI: 10.3390/biom6020018
|View full text |Cite
|
Sign up to set email alerts
|

Trying on tRNA for Size: RNase P and the T-box Riboswitch as Molecular Rulers

Abstract: Length determination is a fundamental problem in biology and chemistry. Numerous proteins measure distances on linear biopolymers to exert effects with remarkable spatial precision. Recently, ruler-like devices made of noncoding RNAs have been structurally and biochemically characterized. Two prominent examples are the RNase P ribozyme and the T-box riboswitch. Both act as molecular calipers. The two RNAs clamp onto the elbow of tRNA (or pre-tRNA) and make distance measurements orthogonal to each other. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…1a, b ) 13 . Recent structural studies of Stem-I:tRNA complexes have revealed two conserved features of cognate tRNA selection: a sequence-specific interaction between the Specifier sequence and the tRNA anticodon, and a stacking interaction between a double T-loop motif (DTM) and the tRNA elbow that effectively acts as an architectural caliper 14 17 of the long side of the tRNA’s “L” shape (Fig. 1c ).…”
Section: Introductionmentioning
confidence: 99%
“…1a, b ) 13 . Recent structural studies of Stem-I:tRNA complexes have revealed two conserved features of cognate tRNA selection: a sequence-specific interaction between the Specifier sequence and the tRNA anticodon, and a stacking interaction between a double T-loop motif (DTM) and the tRNA elbow that effectively acts as an architectural caliper 14 17 of the long side of the tRNA’s “L” shape (Fig. 1c ).…”
Section: Introductionmentioning
confidence: 99%
“…3d). This motif is also present in the ribosome L1 stalk and in RNase P where it performs a similar task of recognizing the tRNA elbow (21,(40)(41)(42). Interestingly, bioinformatics and structural modeling analyses of T-box sequences correctly predicted the existence and unusual orientation of this motif, before being experimentally validated by the three crystal structures (43).…”
Section: High-resolution Structures Of T-box Riboswitch Domainsmentioning
confidence: 91%
“…and ) . In addition, a short 2–3‐nt‐long pyrimidine‐rich bulge located between the AG bulge and the Specifier loop acts as a flexible hinge enabling Stem I to act as a tRNA‐measuring caliper . Additional Stem II and Stem IIA/B pseudoknot elements are present 3′ of Stem I in most T‐box riboswitches, such as the tyrS system (Fig.…”
Section: Sequence and Architecture Of T‐box Riboswitchesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, as engineers know, correct distances between objects or catalytic sites must be measured. Molecular rulers are involved in the process (Zhang and Ferré d'Amaré, ). The RulR/YlxR‐RulQ/YlxQ couple (with conserved gene synteny in Firmicutes), with RulQ (MMSYN1_0298) a ruler binding to the widespread RNA structural motif RNA kink turns (K‐turns (Baird et al ., )), bends the helical trajectory of the RNA by 120°, associated to RulR/YlxR, MMSYN1_0299.…”
Section: Functional Identification Of Syn30 Generic Unknowns and Unkmentioning
confidence: 99%